2020
DOI: 10.1101/2020.11.13.20231480
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 vaccine hesitancy and resistance: Correlates in a nationally representative longitudinal survey of the Australian population

Abstract: BackgroundHigh levels of vaccination coverage in populations will be required even with vaccines that have high levels of effectiveness to prevent and stop outbreaks of coronavirus. The World Health Organisation has suggested that governments take a proactive response to vaccine hesitancy ‘hotspots’ based on social and behavioural insights.MethodsRepresentative longitudinal online survey of over 3000 adults from Australia that examines the demographic, attitudinal, political and social attitudes and COVID-19 h… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 18 publications
(34 reference statements)
3
24
0
Order By: Relevance
“…The analysis in the previous section is of the demographic, socioeconomic, and geographic factors associated with vaccine willingness and confidence in January 2021. Some, but not all of the above associations are similar to those found in previous waves of ANUpoll (Edwards et al 2020) and are therefore picking up stable characteristics associated with vaccine willingness (albeit with different magnitudes).…”
Section: Explaining Vaccine Willingness and Changesmentioning
confidence: 54%
See 1 more Smart Citation
“…The analysis in the previous section is of the demographic, socioeconomic, and geographic factors associated with vaccine willingness and confidence in January 2021. Some, but not all of the above associations are similar to those found in previous waves of ANUpoll (Edwards et al 2020) and are therefore picking up stable characteristics associated with vaccine willingness (albeit with different magnitudes).…”
Section: Explaining Vaccine Willingness and Changesmentioning
confidence: 54%
“…We find a significant increase in vaccine hesitancy. In August 2020, 5.5 per cent of adult Australians said that they would definitely not get the vaccine, 7.2 per cent said that they would probably not get the vaccine, 28.7 per cent said that they would probably get the vaccine and 58.5 per cent said that they would definitely get the vaccine (Edwards et al 2020).…”
Section: Vaccine Willingness and Confidencementioning
confidence: 99%
“…This study also found that religious belief is an essential predictor for vaccine acceptance. A longitudinal survey in Australia found that higher religiosity levels were more likely to be hesitant (Edwards et al 2020). Our study also suggests that people previously infected with the COVID-19 infection are almost three times more likely to accept the COVID-19 vaccine than the uninfected population.…”
Section: Discussionmentioning
confidence: 99%
“…The projections assume that those who are hesitant will never receive the vaccine. The specified hesitancy rates are based on the survey data reported by Edwards et al ., 4 and are only applied to general population groups. Border staff, healthcare and aged care workers, aged care residents and adults with a medical condition were assumed to have negligible vaccine hesitancy.…”
Section: Methodsmentioning
confidence: 99%
“…The population-weighted responses were 5.5% definitely not , 7.2% probably not , 28.7% probably yes and 58.5% definitely yes . 4…”
Section: Introductionmentioning
confidence: 99%